Numerical Study of Traffic Pollutant Dispersion within Different Street Canyon Configurations - Yucong Miao; Shuhua Liu; Yijia Zheng; Shu Wang; Yuan Li (Advances in Meteorology)
The objective of this study is to numerically study flow and traffic exhaust dispersion in urban street canyons with different configurations to find out the urban-planning strategies to ease the air pollution. The Computational Fluid Dynamics (CFD) model used in this study—Open Source Field Operation and Manipulation (OpenFOAM) software package—was firstly validated against the wind-tunnel experiment data by using three different k-ε turbulence models. And then the patterns of flow and dispersion within three different kinds of street canyon configuration under the perpendicular approaching flow were numerically studied. The result showed that the width and height of building can dramatically affect the pollution level inside the street canyon. As the width or height of building increases, the pollution at the pedestrian level increases. And the asymmetric configuration (step-up or step-down street canyon) could provide better ventilation. It is recommended to design a street canyon with nonuniform configurations. And the OpenFOAM software package can be used as a reliable tool to study flows and dispersions around buildings.